Marine Debris on New Zealand Beaches - Baseline Data to Evaluate Regional Variances - van Gool, Ella; Campbell, Marnie; Wallace, Pip; Hewitt, Chad L. (Frontiers in Environmental Science, 2021)
Terrestrial sources of marine debris on beaches are substantial, increasing, and are primarily a result of mismanaged waste on land. The scale, source, and composition of beached marine debris in New Zealand was determined by surveying 41 beaches, with triplicate belt transects, across the North and South Islands. Results demonstrated a significant spatial variance, with the South Island showing a significantly higher mean density than the more populated North Island by count as well as by weight. The majority of all anthropogenic marine debris detected was plastic and arrived through the water. Explanations for regional variances in debris presence are difficult to ascertain with certainty but could not be explained by population density and proximity. These findings contribute to the understudied field of marine debris research in New Zealand and the Southern Hemisphere and provide a starting point for evidence-based mitigation. Recommended changes to future monitoring programs are made. This first national baseline study of marine debris in New Zealand serves as a reference for follow-up studies, including research at other locations.